Fixation of orbicularis oculi muscle and orbital septum to pretarsal fascia and correction of blepharoptosis in construction of double eyelids. Issue 4 (April 2020) - Dong, Ziying; Meng, Pingping; Zhang, Lei; Chen, Zhenyu
Objective: This study was performed to evaluate a novel method of constructing double eyelids by fixation of the orbicularis oculi muscle and orbital septum to the pretarsal fascia and correction of blepharoptosis. Methods: In total, 285 patients requesting aesthetic construction of double eyelids were divided into three groups: those treated by the modified method (Group A, n = 108), those treated by traditional construction of the upper eyelid (Group B, n = 85), and those treated by the Park method (Group C, n = 92). The patients were followed up for 3 to 12 months (average, 6 months). The surgical effects and degree of satisfaction were compared among the three groups. Results: In Group A, the mean operative time was 1.0 ± 0.2 hours. The degree of satisfaction with the surgical effect was significantly different between Group A (95.37%) and Group B (87.06%). However, no significant difference in satisfaction was noted between Group A (95.37%) and Group C (91.30%) or between Group B (87.06%) and Group C (91.30%). Conclusions: The modified technique is simple and effective for construction of double eyelids and correction of blepharoptosis. All patients were satisfied with the surgical and aesthetic effects.